CLASSIC AND MODIFIED BARR’S TECHNIQUE OF ANTERIOR TRANSFER OF THE TIBIALIS POSTERIOR TENDON IN IRREPARABLE PERONEAL PALSIES - Salihagić, Sanela (Bosn J Basic Med Sci, 2008)
Peroneal palsy with loss of active dorsal flexion in foot can be surgically treated by anterior transfer of tibialis posterior tendon. Two techniques are available, classic and modified Barr’s technique of the anterior transfer of tibialis posterior tendon, with different place of tendon’s reinsertion. The aim of the study is evaluation of the degree of active dorsal flexion in foot, and appearance of varus position and hipercorrection of the foot, by comparing the results of the two operative techniques. The study included 40 patients with peroneal irreparable palsies, divided into two equally sized groups. The first group was treated by classic Barr’s technique. The other group of patients was treated by modified Barr’s technique. The group treated by modified Barr’s technique exhibited better functional results. Active dorsal flexion achieved between 95o (in 35% cases) and 90o (in 50% cases), while varus position and hipercorrection of the foot were absent. In the second group of 20 patients, treated by classic Barr’s technique, 80o (40%) and 90o (25%) of active dorsal flexion, indicated worse functional postoperative results. Active dorsal flexion of 70o achieved by this method in two cases (10%), represents unsatisfactory functional result. Varus position of the foot was recorded in 5 cases (25%) and hipercorrection in 4 cases (20%). Modified Barr’s technique is surgical method with better functional and postoperative results in treatment of irreparable peroneal palsy